Faktor-Faktor yang Berhubungan dengan Kepatuhan Berobat Pasien Diabetes Melitus Tipe 2 di Puskesmas Tumpaan - Juan J. Rumondor; Grace Debbie Kandou; Wulan Pingkan Julia Kaunang (Pusat Riset dan Inovasi Nasional, 2025)
This study investigates the factors associated with medication adherence among patients with type 2 diabetes mellitus (T2DM) at Puskesmas Tumpaan, Indonesia. The study aims to identify the influence of knowledge, comorbidities, and family support on patients' adherence to prescribed medication regimens. A cross-sectional design was employed with 205 respondents selected through purposive sampling. Data were collected using structured interviews and validated instruments: MMAS-8 for adherence and DKQ-24 for knowledge. Statistical analyses included chi-square and multivariate logistic regression. Results revealed that 56.1% of patients were adherent to their medication, with knowledge, presence of comorbidities, and family support significantly associated with adherence (p < 0.05). Patients with good knowledge were nearly seven times more likely to adhere, while those with comorbidities and strong family support also demonstrated significantly higher adherence. The findings suggest that enhancing patient education and involving families in chronic care management may improve adherence outcomes. This study underscores the multidimensional nature of adherence and its implications for primary health service programs in diabetes management.